colonization patterns of different fungi on roots of Cymbidium hybridum plantlets and their respective inoculation effects on growth and nutrient uptake of orchid plantlets - Zhao, Xiao-Lan; Yang, Jing-Ze; Liu, Shu; Chen, Chun-Li; Zhu, Hai-Yan; Cao, Jun-Xi (World journal of microbiology & biotechnology, 2014)
Cymbidium hybridum is one of the most popular pot orchids and cut flowers worldwide. However, the long vegetative growth period and the discordant blooming retarded its mass production. The mixotrophic nutritional mode of some chlorophyllous Cymbidium suggested the essential role of mycorrhizal fungi in the growth of adult green orchids. Here 34 root-associated endophytes were obtained from wild and cultivated Cymbidium and eight strains exhibited obvious growth-promoting effects on the C. hybridum plantlets with increasing root number, root diameter or new bud initiation. Among these, three isolates CL01, ZH3A-3 and CY5-1 with distinct cultural traits and colonization patterns showed better growth-promoting effects. Internal transcribed spacer sequence analyses and morphological observation revealed isolate CL01 belonged to Tulasnella-like Rhizoctonia, ZH3A-3, Umbelopsis nana and CY5-1, Scytalidium lignicola. Microscopic study showed isolate CL01 formed typical orchid mycorrhiza and isolate CY5-1 formed pseudo-mycorrhiza with orchid, whereas hyphae of isolate ZH3A-3 aggregated in the host velamen cells at regular intervals and caused the hypertrophied nucleus and aggregated cytoplasm of neighboring host cell. These three isolates significantly enhanced the increased percentage of total fresh weight of plantlets compared with un-inoculated control (83, 99 and 75 %, respectively). In addition, isolate CL01 increased the N, P, Zn, Cu, Fe contents and ZH3A-3 significantly improved K, Ca, Cu, Mn contents of the symbiotic plantlets compared with control. These results suggested that the mass production of C. hybridum and related orchids could be improved by different beneficial fungi from its parents.